P–284 Changes in protein expression due to metformin treatment and hyperinsulinemia in a human endometrial cancer cell line. (6th August 2021) - Lange, C; Machad. Weber, A; Schmidt, R; Schroeder, C; Strowitzki, T; Germeyer, A
Abstract: Study question: The aim of the study was to identify new target proteins/pathways that are affected by metformin treatment in endometrial cancer cells in a proteomic approach. Summary answer: The expression of 1, 300 different proteins were investigated, of which 80 proteins with the most prominent changes were presented and some discussed in detail. What is known already: The incidence of endometrial cancer (EC) has increased over the past years. Metabolic diseases such as obesity, type II diabetes mellitus (T2DM), and associated conditions (i.e. polycystic ovary syndrome (PCOS), insulin resistance) lead to elevated levels of circulating estrogens, which promote EC development and progression. Metformin, an insulin-sensitizing biguanide drug, commonly used in the treatment of T2DM, especially in obese patients, displayed anti-cancer effects in various cancer types, including EC. Different proteins and pathways have been suggested as potential targets, but the underlying mechanism of action of metformin's anti-cancer activity is still not completely understood. Study design, size, duration: In the present in vitro study, EC cells were cultured in 5.5 mmol/L glucose medium (supplemented with 10 nmol/L ß-estradiol (E2)) and treated with metformin (0.5 mmol/L), insulin (100 ng/mL), or remained untreated for 7 d. The expression of 1, 300 different proteins was detected in cellular extracts in an affinity proteomic approach and compared between the treatment groups in order to identify potential target proteins and pathways that contribute to the anti-cancer effects of metformin. Participants/materials, setting, methods: The study was carried out with the EC cell line HEC–1A that represents a postmenopausal model with low E2 sensitivity. Proteins were extracted, quantified with the BCA assay, and protein expression was analyzed using the scioDiscover antibody microarray. Differences in protein abundance between samples were presented as log2-fold changes (log2FC) with significance for samples that displayed |log2FC| ≥ 0.5 and adjusted p ≤ 0.05. Pathway analysis was carried out with the STRING and DAVID databases. Main results and the role of chance: The data revealed that metformin and insulin targeted similar pathways in the present study and mostly acted on proteins related to proliferation, migration and tumor immune response. These pathways may be affected in a tumor-promoting as well as a tumor-suppressing way by either metformin treatment or insulin supplementation. Results for the 80 most affected proteins were presented and the consequences for the cells resulting from the detected expression changes were discussed in detail for several proteins. The presented data helps identify potential target proteins and pathways affected by metformin treatment in EC and allows for a better understanding of the mechanism of action of the biguanide drug's anti-cancer activity. However, further investigations are necessary to confirm the observations and conclusions drawn from the presented data after metformin administration, especially for proteins that were regulated in a favorable way, i.e. AKT3, CCND2, CD63, CD81, GFAP, IL5, IL17A, IRF4, PI3, and VTCN1. Further proteins might be of interest, where metformin counteracted unfavorable effects that have been induced by hyperinsulinemia. Limitations, reasons for caution: The results were obtained from an in vitro study with human cancer cell lines, and thus cannot be easily extrapolated to patients. Wider implications of the findings: In the context of a hyperinsulinemic environment, further proteins might be of interest, i.e. AMFR, CCND2, CD63, ERBB3, EZR, GFAP, IRF4, PI3, PLCG2, SORL1, VEGFA, VTCN1, SPP1, and TM9SF2. Here, a metformin-induced insulin-sensitization might be able to counteract unfavorable effects on protein expression profile that have been induced by hyperinsulinemia. Trial registration number: Not applicable